Fiscal stabilization in oil and gas contracts – evidence and implications - Mansour, M; Nakhle, C (Oxford Institute for Energy Studies, 2016)
The objective of this paper is to analyse how contractual stabilization devices have evolved since the late 1990s, based on a survey of 20 countries and a review of the literature and evidence on stabilization clauses. Although fiscal stability is a commonly cited attribute of a desirable upstream petroleum regime, one of the commonly observed features of existing regimes is the lack of stability. The paper studies the major triggers that push host governments to revise the fiscal terms to which they originally agreed with investors; amongst various economic and political factors, one of the obvious drivers is the oil price. Chasing the price of oil, however, is a burdensome and inefficient strategy, as oil is an internationally traded commodity where short-term price volatility is the norm. The paper’s three broad conclusions include: First, classical stabilization models have not been successful in practice; Second, the more modern clauses are more likely to treat changes in fiscal terms symmetrically, and may be equally beneficial to governments and oil companies; Third, modern stabilization clauses can allow policymakers to consider the overall tax system and its impact on revenue and growth, without worrying about the specific impact on the oil and gas sector, and without penalizing investors in the sector. Fiscal stability clauses in developing countries will remain a key feature of contractual agreements and oil and gas laws for years to come. However, the effectiveness of the more modern clauses in achieving the desired outcome remains as questionable as that of previous stability models, particularly in countries which continue to lack the administrative capability to enforce these mechanisms, and where government policy in general and investment laws and the judiciary in particular lack credibility.